Shoe dog a memoir by the creator of NIKE - Knight, Philip (New York Simon & Schuster, 2017)
In this candid and riveting memoir, for the first time ever, Nike founder and CEO Phil Knight shares the inside story of the company's early days as an intrepid start-up and its evolution into one of the world's most iconic, game-changing, and profitable brands.
Keywords: Knight, Philip H., 1938-